Childhood Behavior and Adult Criminality: Cluster Analysis in a Prospective Study of African Americans - Juon, Hee-Soon (Journal of quantitative criminology, 2006)
Adult criminality has important roots in childhood. While many studies have established that multiple problem behaviors in childhood increase the likelihood of future crime and deviance, the current study extends this “established” relationship by asking three questions: (1) Do different combinations of childhood behavioral risk factors affect adult offending? (2) Do family risk factors affect adult offending above and beyond these combinations of risks?, and (3) Are there gender differences present with respect to these two questions? Gender-specific cluster analyses identified seven clusters of childhood behavioral patterns based on teacher ratings measured in first grade among an epidemiologically-defined cohort of African Americans. Multinomial logistic regression analyses were utilized to examine the relationship of cluster membership, family risks, and criminal arrests through age 32 for serious violent and property crimes. While some gender differences emerged, both males and females in the multiple problem cluster were more likely to have later arrests for serious crime. Females who were frequently punished as first graders were most likely to have later arrests for serious crimes, while males who were from mother-only families were at higher risk of having serious criminal arrests compared to those from mother–father families. Implications for prevention and intervention strategies are also discussed.